Bioavailability of metallic impurities in carbon nanotubes is greatly enhanced by ultrasonication - Toh, Rou Jun (2013)
Metallic impurities within carbon nanotubes (CNTs) are considered as the main cause of their toxicity. Ultrasonication is a common procedure used to purify and obtain homogeneous dispersions of CNTs as well as to mix them with other components for further processing into composites. Herein, the influence of ultrasonication upon the bioavailability of metallic impurities in CNTs was investigated. We showed that even ultrasonication times as short as 5 min significantly enhanced the bioavailability of metallic impurities, which can therefore interact more actively with biologically important molecules. These findings will have profound impact on the processing of CNTs as well as on nanotoxicity studies.